The Kerlan-Jobe Orthopaedic Clinic Shoulder & Elbow Score used as a Patient-Reported Outcome Measure for the Youth and High School Aged Baseball Athlete - Ryan Monti; Alicia Fernandez-Fernandez (International Journal of Sports Physical Therapy)
# Background